Neko ‘Cat’ in Japanese Idioms (Meaning and Figure of Speech Analysis) - Gapur, Abdul; Taulia; Pujiono, Mhd. (International Journal of Culture and Art Studies, 2019)
Generally, idioms are formed with words related to the sense of taste, human body, color, numbers, growth, natural objects and animals. In this study, a Japanese idiom that is formed from neko â€˜catâ€™ is discussed. This study is a qualitative research that aims to find out the lexical and idiomatical meaning of the idiom containing word neko and the figure of speech. The data are idioms with the word neko in 101 Japanese Idioms by Michael L. Maynard, and website (https://dictionary.goo.ne.jp). The results are that 13 idioms that use neko. Some idioms have a difference between lexical and idiomatic meaning. However, there is a link between the lexical and idiomatical meaning with the cultural and historical approach of the lexical used. Data contained in the 8 figure of speech Metaphor, namely neko mo shakushi mo (çŒ« ã‚‚ æ“ å ã‚‚), neko ni koban (çŒ«ã«å°åˆ¤), neko no hitai (çŒ«ã®é¡), neko ni matatabi (çŒ«ã«ã¾ãŸãŸã³), neko in katsuobushi (çŒ«ã«é°¹ç¯€), neko no kubi ni suzu o tsukeru (çŒ«ã®é¦–ã«éˆ´ã‚’ä»˜ã‘ã‚‹), neko no ko ippiki inai (çŒ«ã®åä¸€åŒ¹ã„ãªã„), neko o koroseba shichidai tataru (çŒ«ã‚’æ®ºã›ã°ä¸ƒä»£ç¥Ÿã‚‹. Then 5 figure of speech are included in metonymy, namely neko no te mo karitai (çŒ«ã®æ‰‹ã‚‚å€Ÿã‚ŠãŸã„), neko o kaburu (çŒ« ã‚’ ã‹ ã¶ ã‚‹), karite kita neko (å€Ÿã‚Šã¦ããŸçŒ«), neko o ou yori sakana o noke yo (çŒ«ã‚’è¿½ã†ã‚ˆã‚Šéšã‚’ã®ã‘ã‚ˆ), and neko o ou yori sara o hike (çŒ«ã‚’è¿½ã†ã‚ˆã‚Šçš¿ã‚’å¼•ã‘).